Semen IgM, IgG1, and IgG3 Differentially Associate With Pro-Inflammatory Cytokines in HIV-Infected Men - Pillay, Thevani; Sobia, Parveen; Olivier, Abraham Jacobus; Narain, Kapil; Liebenberg, Lenine J. P.; Ngcapu, Sinaye; Mhlongo, Mesuli; Passmore, Jo-Ann S.; Baxter, Cheryl; Archary, Derseree (Frontiers in Immunology, 2019)
Genital inflammation significantly increases the risk for HIV infection. The seminal environment is enriched in pro-inflammatory cytokines and chemokines. Here, we investigated the interplay between semen cytokines and humoral immunity to understand whether the characteristics of semen antibodies are associated with genital inflammation. In 36 HIV-infected and 40 HIV-uninfected mens’ semen, HIV-specific antibodies (gp120, gp41, p66 and p24), immunoglobulin (Ig) subclasses, isotypes and cytokines, using multiplex assays, were measured. Semen IgG1, IgG3 and IgM were significantly higher in HIV-infected compared to HIV-uninfected men (p<0.05). In HIV-uninfected men, pro-inflammatory cytokines IL-6, IL-8 and MCP-1 significantly correlated with IgG1 and total IgG (IgG1+IgG2+IgG3+IgG4) (both r>0.55; p<0.001). Total IgG in HIV-infected men correlated to HIV-specific antibodies in the semen irrespective of antiretroviral (ARV) use. In HIV-infected, ARV-treated men, p66 and gp41-specific antibodies were inversely correlated with IL-6 and MIP-1α (both r>-0.65, p<0.03). In HIV-infected, ARV-naïve men, p24 and gp120-specific antibodies correlated significantly with pro-inflammatory TNF-α (r>0.44, p<0.03), while p24 antibodies correlated significantly with chemokine MIP-1β (r=0.451; p=0.024). Local cytokines/chemokines were associated with the mucosal-specific Ig subclasses which likely effect specific antibody functions. Together, these data inform on mucosal-specific immunity that may be elicited in the male genital tract in future vaccines and/or combination HIV prevention strategies.